En honor al bicentenario de Francisco Antonio de Zela y el primer grito libertario - Arévalo Vergara, Alexis Rolando (Mercurio Peruano, 2020)
This year we remember the Bicentenary of the First Libertarian Peruvian Shout (Tacna, June 20th, 1811), conducted by the brave patriot Francisco Antonio de Zela and Arizaga. Though the Tacna´s revolt was ephemeral, it did manage to cause a great impact on the Viceroyalty of Peru; demonstrating undoubtedly that the Peruvians took an active part in the independence processes that were simultaneously taking place in all of America. To this respect, the present article will show that it was not the celebrated San Martin and Bolivar who woke the spirit of freedom up in Peru; but that the spirit had been brewing for at least a decade.